Islamic Psychotherapy: Insights from Diverse Psychological Perspectives - Mukhammad Ibnu Syifa; Tesa Nurul Huda (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2024)
Islamic psychotherapy is presented as a holistic approach that integrates spiritual values in clinical practice to overcome psychological problems. The aim of this study is to review the concept and application of Islamic psychotherapy in various psychological perspectives. By using the literature review method, this study tries to explain the relationship between Islamic psychotherapy and various psychological perspectives in overcoming psychological problems. Islamic psychotherapy which has a strong foundation based on the Qur'an and Sunnah has relevance to various psychological perspectives, such as clinical, educational, social, industrial, organizational, and developmental psychology. Islamic psychotherapy does not only focus on healing symptoms, but also on strengthening spirituality and developing individual potential. This study provides insight for mental health professionals, academics, and the general public about the potential of Islamic psychotherapy in improving psychological well-being.